2017
DOI: 10.1186/s12951-017-0247-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vitro angiogenic behavior on anodized titanium dioxide nanotubes

Abstract: BackgroundNeovascularization over dental implants is an imperative requisite to achieve successful osseointegration onto implanted materials. The aim of this study was to investigate the effects on in vitro angiogenesis of anodized 70 nm diameter TiO2 nanotubes (NTs) on Ti6Al4V alloy synthesized and disinfected by means of a novel, facile, antibacterial and cost-effective method using super oxidized water (SOW). We also evaluated the role of the surface roughness and chemical composition of materials of materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 90 publications
2
44
0
2
Order By: Relevance
“…6 Moreover, TiO 2 nanotubes can reduce the inflammatory response of macrophages by inhibiting the nuclear factor-κB (NF-κB) pathway, 7 and TiO 2 is easily formed on the material surface through a simple electrochemical process. 8,9 Interestingly, highly ordered TiO 2 nanotubes with a diameter of about 70 nm improve human umbilical vein endothelial cell (HUVEC) adhesion, proliferation, and angiogenesis, 10 indicating that the morphology of biomaterials is relevant to bodily responses. Although endothelial cells can be guided by titanium nanotubes, [11][12][13] the interaction between the effects of nanotubes on macrophages and the functions of endothelial cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, TiO 2 nanotubes can reduce the inflammatory response of macrophages by inhibiting the nuclear factor-κB (NF-κB) pathway, 7 and TiO 2 is easily formed on the material surface through a simple electrochemical process. 8,9 Interestingly, highly ordered TiO 2 nanotubes with a diameter of about 70 nm improve human umbilical vein endothelial cell (HUVEC) adhesion, proliferation, and angiogenesis, 10 indicating that the morphology of biomaterials is relevant to bodily responses. Although endothelial cells can be guided by titanium nanotubes, [11][12][13] the interaction between the effects of nanotubes on macrophages and the functions of endothelial cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…К настоящему моменту был выполнен ряд исследований, выявивших положительное воздействие нанотрубчатого TiO 2 как на рост клеток, так и на скорость образования гидроксиапатита [7,9,10]. Формирование в результате анодирования нанотрубча-того слоя TiO 2 приводит к увеличению удельной по-верхности имплантата, улучшает коррозионную стой-кость, способствует гидрофильности и, таким образом, значительно улучшает биосовместимость по сравнению с немодифицированными поверхностями [15].…”
Section: (поступило в редакцию 16 января 2018 г)unclassified
“…К настоящему моменту был выполнен ряд исследований, выявивших положительное воздействие нанотрубчатого TiO 2 как на рост клеток, так и на скорость образования гидроксиапатита [7,9,10]. Формирование в результате анодирования нанотрубча-того слоя TiO 2 приводит к увеличению удельной по-верхности имплантата, улучшает коррозионную стой-кость, способствует гидрофильности и, таким образом, значительно улучшает биосовместимость по сравнению с немодифицированными поверхностями [15].Известен ряд работ, посвященных формированию био-активных оксидных покрытий на поверхности так на-зываемых пористых титановых матриц (porous titanium scaffold), полученных различными методами [2,3]. С этой целью применялось как плазменно-электролитическое оксидирование (ПЭО) [16,17], так и электрохимиче-ское анодирование [10].…”
unclassified
“…Although excessive generation of ROS can cause harmful effects, ROS at optimum dose exerts favorable role in angiogenesis and wound healing . Studies also showed that anodized titanium dioxide nanostructures on implants enhance angiogenesis related cellular responses such as higher endothelial cell adhesion, viability, and proliferation . However, a detailed investigation on the angiogenic potential of TiO 2 nanostructures yet to be explored using in ovo or in vivo models.…”
Section: Introductionmentioning
confidence: 99%